Chronic exposure of the freshwater alga Pseudokirchneriella subcapitata to five oxide nanoparticles: Hazard assessment and cytotoxicity mechanisms - Sousa, Cátia A. (2019)
The increasing use of nanoparticles (NPs) unavoidably enhances their unintended introduction into the aquatic systems, raising concerns about their nanosafety. This work aims to assess the toxicity of five oxide NPs (Al2O3, Mn3O4, In2O3, SiO2 and SnO2) using the freshwater alga Pseudokirchneriella subcapitata as a primary producer of ecological relevance. These NPs, in OECD medium, were poorly soluble and unstable (displayed low zeta potential values and presented the tendency to agglomerate). Using the algal growth inhibition assay and taking into account the respective 72 h-EC50 values, it was possible to categorize the NPs as: toxic (Al2O3 and SnO2); harmful (Mn3O4 and SiO2) and non-toxic/non-classified (In2O3). The toxic effects were mainly due to the NPs, except for SnO2 which toxicity can mainly be attributed to the Sn ions leached from the NPs. A mechanistic study was undertaken using different physiological endpoints (cell membrane integrity, metabolic activity, photosynthetic efficiency and intracellular ROS accumulation). It was observed that Al2O3, Mn3O4 and SiO2 induced an algistatic effect (growth inhibition without loss of membrane integrity) most likely as a consequence of the cumulative effect of adverse outcomes: i) reduction of the photosynthetic efficiency of the photosystem II (ФPSII); ii) intracellular ROS accumulation and iii) loss of metabolic activity. SnO2 NPs also provoked an algistatic effect probably as a consequence of the reduction of ФPSII since no modification of intracellular ROS levels and metabolic activity were observed. Altogether, the results here presented allowed to categorize the toxicity of the five NPs and shed light on the mechanisms behind NPs toxicity in the green alga P. subcapitata.